Sentinel Lymph Node Biopsy in Breast Cancer: A Clinical Review and Update - Zahoor, Sheikh; Haji, Altaf; Battoo, Azhar; Qurieshi, Mariya; Mir, Wahid; Shah, Mudasir (Journal of breast cancer, 2017)
Sentinel lymph node biopsy has become a standard staging tool in the surgical management of breast cancer. The positive impact of sentinel lymph node biopsy on postoperative negative outcomes in breast cancer patients, without compromising the oncological outcomes, is its major advantage. It has evolved over the last few decades and has proven its utility beyond early breast cancer. Its applicability and efficacy in patients with clinically positive axilla who have had a complete clinical response after neoadjuvant chemotherapy is being aggressively evaluated at present. This article discusses how sentinel lymph node biopsy has evolved and is becoming a useful tool in new clinical scenarios of breast cancer management.